2001
DOI: 10.1515/hf.2001.035
|View full text |Cite
|
Sign up to set email alerts
|

Thermomechanical (TMP) and Chemo-Thermomechanical Pulps (CTMP) for Medium Density Fibreboards (MDF)

Abstract: Summary Thermomechanical (TMP) and chemo-thermomechanical pulps (CTMP) were prepared from spruce under different pulping conditions. The fibres were dried at 70 °C and medium density fibreboards (MDF) were made therefrom in pilot plant scale using urea-formaldehyde resins as a binder. The results of testing the physical-mechanical properties reveal that the pulping temperature has a significant influence on the thickness swelling and water absorption of the boards. MDF prepared from fibres produced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 1 publication
0
12
0
2
Order By: Relevance
“…After this, the fibers are commonly treated with thermosetting resins and pressed to boards with high strength and low swelling when exposed to water (Widsten et al 2004). Furthermore, higher pulping temperature (180°C compared with 140°C and 160°C) has been reported to result in reduced swelling and water absorption of boards (Roffael et al 2001). The objective of the present article is to characterize fibers derived from HT-TMP in the context of SEC values of the process, focusing on morphology, bonding ability, and surface composition of the fibers in view of their possible application in fiber-reinforced composites.…”
Section: Introductionmentioning
confidence: 99%
“…After this, the fibers are commonly treated with thermosetting resins and pressed to boards with high strength and low swelling when exposed to water (Widsten et al 2004). Furthermore, higher pulping temperature (180°C compared with 140°C and 160°C) has been reported to result in reduced swelling and water absorption of boards (Roffael et al 2001). The objective of the present article is to characterize fibers derived from HT-TMP in the context of SEC values of the process, focusing on morphology, bonding ability, and surface composition of the fibers in view of their possible application in fiber-reinforced composites.…”
Section: Introductionmentioning
confidence: 99%
“…Ten random samples for 24 h thickness swell (TS) tests (TS % , European standard 1993) were cut from produced HDF boards following European standard 1994. TS was chosen because of its susceptibility to hemicelluloses (Roffael et al 2001 ). Table 1 contains a descriptive summary of all variables considered in the models.…”
Section: Methodsmentioning
confidence: 99%
“…Krug and Kehr (2001) reported that increasing the steam pressure resulted in shorter fiber lengths, lower strength, and lower elastic properties but improved long-term swelling properties. Roffael et al (2005) found that high pulping temperature resulted in lower TS and WA of MDF panels. The results from Deng et al (2006) and Xing (2006) indicated that both MOE and MOR could be improved when refining steam pressure increases.…”
Section: Introductionmentioning
confidence: 96%